Is West Africa single currency a tool for economy transition? - Emmanuel Ayeni; Oluwaseyi Fanibuyan; Kayode Muhammed Ibrahim; Iskil Adewale Mobolaji (Research in Globalization, 2023)
Economy integration among countries of the world is seen as a key to drive economic growth and development through favourable policies among members. The study examines the impact of a single currency on the economy of West Africa States. Findings show that gross domestic product growth rate, degree of openness, and political stability have impacted the single currency competitiveness both among the member countries and globally. However, the possible advantage of a single currency would be annihilated by unfavourable terms of trade, government ineffectiveness, and weak regulatory quality. The study thereby recommended that the single currency in the region would not benefit member countries in the short run but a possibility exists in the long run as a result of the cointegration relationship among variables used in the study.
Keywords: 330; Economic integration; Member countries